Sustainable and Fair Technology for an Equitable Society - Essa, Nabeela Ebrahem; Mardikaningsih, Rahayu (Journal of Social Science Studies, 2023)
Technological innovation has great potential to solve global problems, but its implementation must be carried out with attention to environmental sustainability and social justice. Technology that is not designed with consideration for both aspects can exacerbate social inequality, damage the environment, and create disparities in access to resources. Therefore, policies are needed to guide the development and application of technology with principles of sustainability and justice, to ensure that its benefits can be felt by all layers of society. A more inclusive and sustainability-based approach can make technology a tool for creating relevant, fair, and responsible solutions. This involves collaboration between the government, technology developers, and society in formulating policies that promote environmentally friendly technology, accessible to many, and do not endanger individual rights. The sustainability of technology is not only related to economic efficiency or technical advancement but also to the moral and ethical aspects that are crucial for achieving collective well-being. The implementation of fair and sustainable technology is a key factor in realizing a better and more sustainable future.